Participatory Integrated Climate Services for Agriculture (PICSA) methods and materials scale out to 17 countries, reaching 140,850 farmers in Africa, Latin America and Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CCAFS supported the development and scaling up of the PICSA approach through funding for methodology testing and innovation, development of the PICSA Field Guide, resource mobilization, and project implementation. Through CCAFS and other University of Reading partnerships, PICSA has been scaled out to 17 countries in Africa, Latin America and Asia reaching 140,850 farmers and more than 2,000 intermediaries.